Thermoelectric conversion materials and thermoelectric conversion elements
A thermoelectric conversion material combining a compound of general formula (1) with carbon nanotubes and poly(meth)acrylonitrile polymer addresses the challenge of low conductivity in organic materials, enhancing both performance and conductivity in thermoelectric elements.
Patent Information
- Application Number
- JP2021172856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-10-22
AI Technical Summary
Existing thermoelectric conversion materials, particularly those using organic compounds, face challenges in achieving both high thermoelectric conversion performance and electrical conductivity, as exemplified by low electrical conductivity in previous inventions.
A thermoelectric conversion material comprising a compound represented by general formula (1) and/or its salt, combined with a conductive material and a polymer, specifically utilizing a conductive material like carbon nanotubes and a polymer such as poly(meth)acrylonitrile, to enhance both thermoelectric conversion performance and electrical conductivity.
The material achieves improved thermoelectric conversion performance and electrical conductivity, resulting in a high-quality thermoelectric conversion element with excellent flexibility and stability.
Smart Images

Figure 0007655187000001 
Figure 0007655187000002 
Figure 0007655187000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion material and a thermoelectric conversion element. [Background technology]
[0002] Thermoelectric conversion technology, which converts heat into electricity using thermoelectric conversion materials, has been attracting attention as a clean energy source that can effectively utilize minute thermal energy such as body heat and exhaust heat from factories, cars, and homes, as well as various types of heat in nature, as electricity. There are various thermoelectric effects that are used in thermoelectric conversion technology, but the mainstream system uses the Seebeck effect, in which an electromotive force is generated by an electron gradient that occurs within a material in response to the temperature difference when two different temperatures are applied to both ends of the material, which is made up of a combination of semiconductors and metals.
[0003] Thermoelectric materials that can convert between thermal energy and electrical energy are used in thermoelectric conversion elements such as thermoelectric power generation elements and Peltier elements. Thermoelectric conversion elements are elements that convert heat into electricity and are made up of a combination of semiconductors and metals. Representative thermoelectric conversion elements are classified into p-type semiconductors alone, n-type semiconductors alone, and combinations of p-type and n-type semiconductors. To obtain a larger potential difference, thermoelectric conversion elements generally use a combination of p-type and n-type semiconductors as materials.
[0004] Thermoelectric conversion elements, such as Peltier elements, are used as thermoelectric modules that combine a number of elements into a plate or cylinder. Because they can directly convert thermal energy into electricity, they can be used, for example, as a power source for wristwatches that operate with body heat, and for power generation on the ground and in artificial satellites. The performance of a thermoelectric conversion element depends on the performance of the thermoelectric conversion material and the durability of the module.
[0005] As described in Non-Patent Document 1, the dimensionless thermoelectric figure of merit ZT is used as an index representing the performance of a thermoelectric conversion material. In addition, the power factor PF (=S 2·σ) may also be used. The dimensionless thermoelectric figure of merit ZT is expressed by the following formula (1). ZT=((S 2 ·σ) / к)·T Equation (1) Here, S is the Seebeck coefficient (V / K), σ is the electrical conductivity (S / m), T is the absolute temperature (K), and κ is the thermal conductivity (W / (m K)). Thermal conductivity κ is expressed by the following formula (2). к=α·ρ·C Equation (2) where α is the thermal diffusivity (m 2 / s), ρ is density (kg / m 3 ), and C is the specific heat capacity (J / (kg K)). That is, in order to improve the thermoelectric conversion performance (hereinafter also referred to as thermoelectric properties), it is important to improve the Seebeck coefficient or electrical conductivity while decreasing the thermal conductivity.
[0006] In recent years, research has been conducted on thermoelectric conversion elements using organic materials instead of conventional inorganic materials. Organic materials are lightweight, have excellent moldability, and are more flexible than inorganic materials, so they are highly versatile within the temperature range in which they do not decompose. In addition, they are more advantageous than inorganic materials in terms of manufacturing energy and costs, as printing technology can be easily used.
[0007] For example, Patent Document 1 discloses a thermoelectric conversion material containing a polymer dispersant having an organic dye skeleton and carbon nanotubes (CNTs), and a thermoelectric conversion element using the same. Patent Document 2 discloses a thermoelectric conversion material containing a conductive compound in which a polycyclic aromatic ring having carrier transport properties is bonded to a substituent containing an alkyl group, and a thermoelectric conversion element using the same. However, the invention of Patent Document 1 does not provide sufficient performance as a thermoelectric conversion element. Also, the invention of Patent Document 2 discloses a thermoelectric conversion material containing a conductive compound in which a polycyclic aromatic ring having carrier transport properties is bonded to a substituent containing an alkyl group, and a thermoelectric conversion element using the same. -7 The electrical conductivity is low at only S / cm, and it is not possible to obtain a practical value for use as a thermoelectric conversion element. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2015 / 050113 [Patent Document 2] International Publication No. 2015 / 129877 [Non-patent literature]
[0009] [Non-Patent Document 1] Takenobu Kajikawa, "Thermoelectric Conversion Technology Handbook (First Edition)", NTS Publishing, p. 19 Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a thermoelectric conversion material that can achieve both thermoelectric conversion performance and electrical conductivity. [Means for solving the problem]
[0011] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention relates to a thermoelectric conversion material comprising a compound (A) represented by the following general formula (1) and / or a salt of compound (A), and a conductive material (B).
[0012] [ka]
[0013] [In general formula (1), R 1 ~R 5 R each independently represents a hydrogen atom, an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent. 1 and R 2 or R 3 and R 4 may be bonded to each other to form a ring, but R 1 and R 2and R 3 and R 4 But they never form a ring at the same time.]
[0014] The present invention also relates to the above thermoelectric conversion material, which further comprises a polymer (C).
[0015] The present invention also relates to the above thermoelectric conversion material, wherein the polymer (C) is a copolymer containing monomer units derived from (meth)acrylonitrile.
[0016] The present invention also relates to the above thermoelectric conversion material, wherein the content of the polymer (C) is 5 to 100 mass % based on the total amount of the conductive material (B).
[0017] The present invention also relates to a thermoelectric conversion element comprising a thermoelectric conversion film containing the above-mentioned thermoelectric conversion material and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other. Effect of the Invention
[0018] The present invention provides a thermoelectric conversion material that can achieve both thermoelectric conversion performance and electrical conductivity. In addition, the material can be used to provide a thermoelectric conversion element that is excellent in thermoelectric conversion performance and electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described. In this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acrylo", "(meth)acrylic acid", "(meth)acrylate", and "(meth)acryloyloxy" refer to "acrylic or methacrylic", "acrylo or methacrylo", "acrylic acid or methacrylic acid", "acrylate or methacrylate", and "acryloyloxy or methacryloyloxy", respectively.
[0020] <Thermoelectric conversion materials> The thermoelectric conversion material of the present invention comprises a compound (A) represented by general formula (1) and / or a salt of compound (A), and a conductive material (B).
[0021] <Compound (A)> The compound (A) is a compound represented by general formula (1). In general formula (1), R 1 ~R 5 each independently represents a hydrogen atom, an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent.
[0022] Examples of the alkyl group in the general formula (1) include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a benzyl group, etc. Among these, a methyl group and an ethyl group are preferable.
[0023] Examples of the alkenyl group in the general formula (1) include a propenyl group, a butenyl group, and a pentenyl group.
[0024] Examples of the aryl group in the general formula (1) include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group.
[0025] The heterocyclic group in the general formula (1) includes, but is not limited to, five-membered heterocyclic groups and six-membered heterocyclic groups. Examples of the five-membered heterocyclic group include a pyrrolyl group, a pyrrolidino group, a thiophenyl group, a thiazolyl group, an oxazolyl group, an imidazolyl group, and a pyrazolyl group. Examples of the six-membered heterocyclic group include a pyridyl group, a quinolyl group, a pyrimidinyl group, a piperidyl group, a pyrazyl group, and a 1,3,5-triazin-2-yl group.
[0026] The alkyl group, alkenyl group, aryl group and heterocyclic group in the general formula (1) may have a substituent. Examples of the substituent include a hydroxyl group, a formyl group, a carbonyl group, a carboxyl group, an ether group, an ester group, an amino group, a carbamoyl group, an azo group, a nitro group, a nitroso group, a sulfanyl group, a sulfo group, and a halogen group. Examples of the halogen group include a fluoro group, a chloro group, a bromo group, and an iodo group. Therefore, for example, a carboxymethyl group, -C(-NH2)=NH, can be regarded as a type of alkyl group having a substituent.
[0027] R 1 and R 2 or R 3 and R 4 may be bonded to each other to form a ring. For example, R 1 and R 2 When and are combined, R 1 and R 2 A group formed by bonding R to R is a divalent group, and examples of such a divalent group include an alkylene group, an alkenylene group, an arylene group, and groups formed by bonding these groups together. Specific examples include an ethylene group, a vinylene group, and a phenylene group. However, R 1 and R 2 and R 3 and R 4 However, they do not form a ring at the same time.
[0028] R 1 is preferably a hydrogen atom. 2 , R 4 is preferably a hydrogen atom or an alkyl group which may have a substituent. 3 , R 5 is preferably a hydrogen atom, an alkyl group which may have a substituent, or an aryl group which may have a substituent.
[0029] The salt of compound (A) means a salt of compound (A) and an acid. Here, examples of the acid include inorganic acids and organic acids. Examples of the inorganic acid include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc., and examples of the organic acid include carboxylic acid and sulfonic acid, etc. Examples of the carboxylic acid include formic acid and acetic acid, and examples of the sulfonic acid include benzenesulfonic acid and p-toluenesulfonic acid, etc.
[0030] Although it is not clear why the use of compound (A) represented by general formula (1) or a salt thereof results in a thermoelectric material with excellent thermoelectric conversion performance, it is presumed that the guanidine structure (N2C=N) in general formula (1) is stably adsorbed to the conductive material (B), improving the thermoelectric conversion performance.
[0031] Therefore, specific examples of compound (A) and its salts include tetramethylguanidine, 1,3-diphenylguanidine, phenylguanidine, glycocyamine, 1-(o-tolyl)biguanide, tizanidine hydrochloride, isocytosine, 2-imino-1-imidazolidineacetic acid, clonidine hydrochloride, etc. Among them, tetramethylguanidine, 1,3-diphenylguanidine, and phenylguanidine are more preferable.
[0032] <Conductive material (B)> The conductive material (B) contributes to improving the conductivity. Therefore, the conductivity can be improved by increasing the content of the conductive material (B). The conductive material (B) is not particularly limited as long as it is a material having conductivity (carbon material, metal material, conductive polymer, etc.), and examples of the carbon material include graphite, carbon nanotubes, carbon black, graphene (including graphene nanoplates), etc. Examples of the metal material include metal powders such as gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, germanium, gallium, and platinum, as well as ZnSe, CdS, InP, GaN, SiC, SiGe, and alloys thereof, and composite powders thereof. In addition, fine particles coated with a core and a material different from the core material, specifically, for example, silver-coated copper powder in which the core material is copper and the surface is coated with silver, can be mentioned. Examples of the conductive polymer include powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), and GZO (gallium-doped zinc oxide), as well as powders surface-coated with these metal oxides. Examples of the conductive polymer include PEDOT / PSS (a composite of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid), polyaniline, polyacetylene, polypyrrole, polythiophene, and polyparaphenylene. The conductive material may be one type or a combination of two or more types. The shape of the conductive material (B) is not particularly limited, and may be amorphous, aggregated, scaly, microcrystalline, spherical, flake, wire, or the like, as appropriate.
[0033] From the viewpoint of achieving both a high Seebeck coefficient and electrical conductivity, at least one selected from the group consisting of carbon nanotubes, carbon black, and graphene (including graphene nanoplates) is preferred, more preferably carbon nanotubes, and particularly preferably single-walled carbon nanotubes.
[0034] Examples of carbon materials include flaky graphite such as CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, and F manufactured by Nippon Graphite Industries Co., Ltd. Examples of the graphite include #2, F#3, BF-3AK, FBF, BF-15AK, CBR, CPB-6S, CPB-3, 96L, 96L-3, K-3, SC-120, SC-60, HLP, CP-150, and SB-1 manufactured by Chuetsu Graphite Industry Co., Ltd., EC1500, EC1000, EC500, EC300, EC100, and EC50 manufactured by Ito Graphite Industry Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. Examples of the spherical natural graphite include CGC-20, CGC-50, CGB-20, and CGB-50 manufactured by Nippon Graphite Industry Co., Ltd. Examples of the amorphous graphite include Blue P, AP, AOP, and P#1 manufactured by Nippon Graphite Industry Co., Ltd., and APR, K-5, AP-2000, AP-6, 300F, and 150F manufactured by Chuetsu Graphite Co., Ltd. Examples of artificial graphite include PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, and HAG-150 manufactured by Nippon Graphite Industries Co., Ltd.; G-4AK, G-6S, G-3G-150, G-30, G-80, G-50, SMF, EMF, SFF, SFF-80B, SS-100, BSP-15AK, BSP-100AK, and WF-15C manufactured by Chuetsu Graphite Co., Ltd.; and SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, and SGX-1 manufactured by SEC Carbon Co., Ltd.
[0035] Examples of commercially available conductive carbon fibers and carbon nanotubes include vapor grown carbon fibers such as VGCF manufactured by Showa Denko K.K.; single-walled carbon nanotubes such as EC1.5 and EC1.5-P manufactured by Meijo Nano Carbon Co., Ltd., TUBALL manufactured by Kusumoto Chemicals Co., Ltd., and ZEONANO manufactured by Zeon Nano Technology Inc.; FloTube9000, FloTube7000, and FloTube2000 manufactured by CNano Corporation; NC7000 manufactured by Nanocyl Corporation; and 100T and 200P manufactured by Knano Corporation.
[0036] Examples of commercially available carbon black include Tokai Carbon's Tokablack #4300, #4400, #4500, and #5500; Degussa's Printex L; and Colombian's Raven7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, Conductex SC ULTRA, and Conductex 975. Examples of the black include ULTRA, PUERBLACK100, 115, and 205, Mitsubishi Chemical Corporation's #2350, #2400B, #2600B, #3050B, #3030B, #3230B, #3350B, #3400B, and #5400B, Cabot Corporation's MONARCH1400, 1300, and 900, VulcanXC-72R, and BlackPearls2000, and TIMCAL Corporation's Ensaco250G, Ensaco260G, Ensaco350G, and SuperP-Li furnace blacks, Lion Corporation's EC-300J, EC-600JD, and other ketjen blacks, and Denki Kagaku Kogyo Co., Ltd.'s Denka Black, Denka Black HS-100, and FX-35, and other acetylene blacks. These are not particularly limited.
[0037] In addition, the content of the conductive material (B) is preferably 15 mass % or more and 90 mass % or less, more preferably 20 mass % or more and 80 mass % or less, and even more preferably 30 mass % or more and 60 mass % or less, based on the total of the compound (A) and / or the salt of the compound (A), the conductive material (B), and the polymer (C).
[0038] <Polymer (C)> The thermoelectric conversion material of the present invention may contain a polymer (C). It is presumed that the inclusion of the polymer (C) improves film-forming properties and film strength, suppresses the flow of the compound (A) and / or a salt of the compound (A) in the thermoelectric conversion material, and enhances the adsorption action to the conductive material (B). Examples of the polymer (C) include, but are not limited to, poly(meth)acrylonitrile, poly(meth)acrylic acid ester, poly(meth)acrylamide, polyurethane, polyvinyl alcohol, polyvinylpyrrolidone, polyvinylpyridine, polystyrene, polyvinyl acetate, polyimide, and polyolefin.
[0039] The polymer (C) preferably contains a nitrogen-containing polymer, more preferably contains a polymer having a nitrogen atom in the side chain, and further preferably contains a polymer containing a vinyl monomer unit having a nitrogen atom in the side chain. Of the polymers containing a vinyl monomer unit having a nitrogen atom in the side chain, it is preferable to contain a polymer containing a monomer unit derived from (meth)acrylonitrile and polyvinylpyrrolidone, and it is preferable to contain a polymer containing a monomer unit derived from (meth)acrylonitrile. Examples of the polymer containing a monomer unit derived from (meth)acrylonitrile include poly(meth)acrylonitrile and a copolymer consisting of a monomer unit derived from (meth)acrylonitrile and another monomer unit. Here, examples of the other monomer include aromatic hydrocarbons having a double bond and (meth)acrylic acid esters. Examples of aromatic hydrocarbons having a double bond include styrene and styrene macromers. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters and (meth)acrylic acid hydroxyalkyl esters. When polymer (C) contains a polymer containing a monomer unit derived from (meth)acrylonitrile, the strong polarity of the cyano group in (meth)acrylonitrile increases its adsorption to conductive material (B), and further increases the adsorption of compound (A) to conductive material (B). As a result, aggregation of conductive material (B) and adsorption of moisture to conductive material (B) are suppressed, and the stability of the thermoelectric conversion material is enhanced.
[0040] The content of the polymer (C) is preferably 5 to 100 mass% based on the total amount of the conductive material (B), more preferably 25 to 100 mass%, further preferably 50 to 100 mass%, and particularly preferably 50 to 80 mass%.
[0041] The molecular weight of the polymer (C), in terms of polystyrene equivalent weight average molecular weight, is preferably in the range of 3000 to 500000, more preferably in the range of 4000 to 200000, further preferably in the range of 5000 to 100000, and particularly preferably in the range of 10000 to 100000. By setting the weight average molecular weight within the above range, the adsorption to the conductive material (B) becomes better.
[0042] (dispersion medium) The dispersion medium can be used as a medium when mixing the compound (A) and / or the salt of the compound (A) with the conductive material (B), or the compound (A) and / or the salt of the compound (A), the conductive material (B), and the polymer (C). The inclusion of the dispersion medium results in an ink or paste state, so that a thermoelectric conversion film can be formed by printing or coating. The dispersion medium that can be used is preferably one that can dissolve or disperse the compound (A) and / or the salt of the compound (A), the conductive material (B), and the polymer (C), and examples of such dispersion medium include organic solvents and water. The dispersion medium may be used alone or in combination of two or more.
[0043] The organic solvent may be appropriately selected as necessary from, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, terpineol, dihydroterpineol, 2,4-diethyl-1,5-pentanediol, 1,3-butylene glycol, isobornylcyclohexanol, ethylene glycol, 1,3-propanediol, 1,4-butanediol, glycerin, trifluoroethanol, m-cresol, and thiodiglycol, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran, dioxane, and ethylene glycol dimethyl ether, hydrocarbons such as hexane, heptane, and octane, aromatic hydrocarbons such as benzene, toluene, xylene, and cumene, esters such as ethyl acetate and butyl acetate, and nitrogen-containing heterocycles such as N-methylpyrrolidone. From the viewpoint of dispersibility and solubility, N-methylpyrrolidone is particularly preferred.
[0044] (Inorganic thermoelectric conversion materials) The thermoelectric conversion material of the present invention may contain an inorganic thermoelectric conversion material as necessary in order to improve the thermoelectric conversion performance. The inorganic thermoelectric conversion material is not particularly limited, and any material generally known as a thermoelectric conversion material can be used.
[0045] <Thermoelectric conversion element> The thermoelectric conversion element of the present invention has a thermoelectric conversion film formed using the thermoelectric conversion material of the present invention and electrodes, and the thermoelectric conversion film and the electrodes are electrically connected. The thermoelectric conversion film is excellent in heat resistance and flexibility in addition to electrical conductivity and thermoelectric properties. Therefore, a high-quality thermoelectric conversion element can be easily produced.
[0046] The thermoelectric conversion film may be a film obtained by applying a thermoelectric conversion material onto a substrate. Since the thermoelectric conversion material has excellent moldability, it is easy to obtain a good film by application or printing. The method for producing the thermoelectric conversion film is not particularly limited as long as the desired thermoelectric conversion film can be obtained, and can be appropriately selected according to the properties of the thermoelectric conversion material, such as viscosity, and the required film thickness, area, shape, and other conditions. For example, methods using various means such as spin coating, spray coating, roll coating, gravure coating, flexo coating, die coating, lip coating, knife coating, blade coating, comma coating, roll coating, curtain coating, bar coating, dip coating, dispenser, screen coating, and inkjet printing can be mentioned.
[0047] The thickness of the thermoelectric conversion film is not particularly limited and can be set according to the required electric properties such as current value, voltage value, and resistance, and thermoelectric properties, but as described later, it is preferable that the film is formed to have a certain thickness or more so that a temperature difference can be generated and transmitted in the thickness direction or surface direction of the thermoelectric conversion film. From the viewpoint of thermoelectric properties and flexibility, the film thickness of the thermoelectric conversion film is preferably in the range of 0.1 to 200 μm, more preferably in the range of 1 to 100 μm, and particularly preferably in the range of 1 to 60 μm.
[0048] The substrate is not particularly limited, and examples of the substrate that can be used include nonwoven fabric, paper, plastic films made of materials such as polyethylene, polyethylene terephthalate (PET), polyethylene naphthalate, polyethersulfone, polypropylene, polyimide, polycarbonate, and cellulose triacetate, and glass, etc. These substrates may have an aluminum deposition layer or a barrier layer on the substrate surface to prevent deterioration of the thermoelectric conversion material due to the effects of water and oxygen.
[0049] In order to improve the adhesion between the substrate and the thermoelectric conversion film, various treatments can be performed on the substrate surface. Specifically, prior to application of the thermoelectric conversion material, UV ozone treatment, corona treatment, plasma treatment, or easy-adhesion treatment can be performed.
[0050] The thermoelectric conversion film may be laminated with a substrate, or may be a free-standing film without a substrate. When preparing a free-standing film, there is no particular limitation, but for example, the film can be obtained by forming the thermoelectric conversion film on a release sheet and then removing the release coat.
[0051] Examples of the release sheet include release-treated plastic films such as polyester film, polyethylene film, polypropylene film, and polyimide film.
[0052] The thermoelectric conversion element can be constructed by applying techniques well known in the art, except that it is constructed using the above-mentioned thermoelectric conversion material. A more specific configuration of the thermoelectric conversion element and a manufacturing method thereof will be described below.
[0053] In a thermoelectric conversion element, a thermoelectric conversion film and an electrode are electrically connected. Here, "electrically connected" means that they are joined to each other or can be electrically connected via other components such as wires.
[0054] The material of the electrode is not particularly limited as long as it functions as an electrode, and can be selected from metals, alloys, and semiconductors. In one embodiment, metals and alloys are preferred because they have high electrical conductivity and low contact resistance of the thermoelectric conversion film. For example, it is preferred that the electrode contains at least one selected from the group consisting of gold, silver, copper, platinum, nickel, and aluminum. It is more preferred that the electrode contains silver.
[0055] The method for forming the electrodes is not particularly limited, and the electrodes can be formed by a method such as vacuum deposition, thermocompression bonding of an electrode material foil or a film having an electrode material film, application of a paste in which fine particles of the electrode material are dispersed, etc. From the viewpoint of process simplicity, a method using thermocompression bonding of an electrode material foil or a film having an electrode material film, or application of a paste in which the electrode material is dispersed is preferred.
[0056] Typical examples of the structure of a thermoelectric conversion element can be broadly classified into (1) a structure in which electrodes are formed on both ends of the thermoelectric conversion film of the present invention, and (2) a structure in which the thermoelectric conversion film of the present invention is sandwiched between two electrodes, based on the positional relationship between the thermoelectric conversion film and a pair of electrodes. The thermoelectric conversion element having the structure (1) above can be obtained, for example, by forming a thermoelectric conversion film on a substrate, and then applying silver paste to both ends of the film to form the first and second electrodes. In this way, a thermoelectric conversion element having electrodes formed on both ends of the thermoelectric conversion film can easily increase the distance between the two electrodes. Therefore, it is easy to generate a large temperature difference between the two electrodes and perform efficient thermoelectric conversion.
[0057] The thermoelectric conversion element having the structure of (2) above can be obtained, for example, by applying silver paste onto a substrate to form a first electrode, forming the thermoelectric conversion film of the present invention thereon, and further applying silver paste onto the first electrode to form a second electrode. In this way, a thermoelectric conversion element having the thermoelectric conversion film of the present invention sandwiched between two electrodes can utilize the temperature difference in the film thickness direction of the thermoelectric conversion film, that is, in the direction perpendicular to the substrate, and can be used in a form attached to a heat source. Therefore, it is preferable because it has the advantage of being able to extract heat from a wide range from the heat source. In the thermoelectric conversion element having the structure of (2) above, it is also possible to ensure a temperature difference by increasing the film thickness to widen the distance between the two electrodes.
[0058] Thermoelectric conversion elements can generate a high voltage by connecting them in series, and can generate a large current by connecting them in parallel. The thermoelectric conversion element may be one in which two or more thermoelectric conversion elements are connected. According to the present invention, since the thermoelectric conversion element has excellent flexibility, it can be well installed so as to conform to a heat source having a shape that is not flat. The thermoelectric conversion element may have a heat absorption layer or a heat storage layer for efficient heat transfer from a heat source, and may also have a heat insulation layer or a heat dissipation layer for ensuring a temperature difference. Furthermore, depending on the application and the amount of power required, the extracted electricity can be boosted using a boost circuit, or the extracted electric energy can be temporarily stored in a condenser, a capacitor, a secondary battery, or the like for use. EXAMPLES
[0059] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass". In addition, "NMP" refers to N-methylpyrrolidone.
[0060] (Method of measuring weight average molecular weight (Mw)) The weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC) equipped with a differential refractive index (RI) detector. The instrument used was an HLC-8320GPC (manufactured by Tosoh Corporation), with three separation columns connected in series, and the packing materials used were Tosoh Corporation's "TSK-GELSUPERAW-4000", "AW-3000" and "AW-2500", respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, at a flow rate of 0.6 mL / min. The measurement sample was adjusted to a concentration of 1% in the dispersion medium consisting of the above eluent, and 20 μL was injected. The molecular weight is a polystyrene equivalent value.
[0061] <Production of Polymer (C)> (Production Example 1) (Production of Polymer (C-1)) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile, 80 parts of acrylonitrile, 20 parts of HEA, and 1 part of 3-mercapto-1,2-propanediol, and substituted with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture consisting of 10 parts of acetonitrile and 0.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-65) was dropped into the reaction vessel over 6 hours to carry out a polymerization reaction. After the dropwise addition, the reaction was carried out at 70°C for 1 hour, and then 0.1 parts of V-65 was added, and the reaction was continued at 70°C for another 1 hour to obtain the target product as a precipitate. Thereafter, it was confirmed that the conversion rate exceeded 98% by measuring the nonvolatile content. The product was filtered out by vacuum filtration, washed with 100 parts of acetonitrile, and the solvent was completely removed by vacuum drying to obtain a polymer (C-1).
[0062] (Production Example 2) (Production of Polymers (C-2 to C-3)) Polymers (C-2 to C-3) were produced in the same manner as in Production Example 1, except that the types and amounts of monomers were changed as shown in Table 2. The Mw of each polymer is shown in Table 2. Polymers (C-2 to C-3) were produced to have a predetermined Mw by appropriately changing the amounts of chain transfer agent and polymerization initiator, reaction conditions, etc. In addition, 3-mercapto-1,2-propanediol was used as the chain transfer agent.
[0063] In Table 2, unless otherwise specified, the numerical values represent "parts", and blank spaces mean that no ingredient was blended. The abbreviations used in this specification are as follows. AN: Acrylonitrile HEA: Hydroxyethyl acrylate St: styrene PME1000: Methoxypolyethylene glycol monomethacrylate (NOF Corporation, Blenmer (registered trademark) PME-1000, number of oxyethylene groups: 23)
[0064] <Production of Dispersion Containing Thermoelectric Conversion Material> [Example 1] (Dispersion 1) 0.1 parts of compound (A-1), 0.4 parts of SWCNT (single-walled carbon nanotube "TUBALL" manufactured by OCSiAl Corporation), and 79.3 parts of NMP were weighed and mixed. Beads were further added, and the mixture was shaken with a Scandex for 4 hours, and then filtered to remove the beads, to obtain a dispersion liquid 1 of a thermoelectric conversion material.
[0065] [Examples 2 to 25, Comparative Example 1] (Dispersion 2~25, 101) Thermoelectric conversion material dispersions 2 to 25 and 101 were obtained in the same manner as dispersion 1, except that the types and amounts of materials were changed as shown in Tables 3 and 4, respectively.
[0066] The abbreviations for the materials in the table are as follows: Conductive material (B) SWCNT: OCSiAl's single-walled carbon nanotube "TUBALL" MWCNT: (Kumho Petrochemical's multi-walled carbon nanotubes "Knanos100P") CB: (Lion Ketjen Black "EC-300J") Polymer (C) PVP: (Nippon Shokubai Polyvinylpyrrolidone "K-30")
[0067] <Evaluation of Thermoelectric Conversion Materials> The obtained dispersions 1 to 25 and 101 were each applied to a 75 μm thick PET film, which was a sheet-like substrate, using an applicator, and then dried at 120° C. for 30 minutes to obtain a laminate having a thermoelectric conversion film with a thickness of 5 μm. The electrical conductivity, Seebeck coefficient, and stability over time of the obtained laminate having a thermoelectric conversion film (hereinafter also referred to as a coating film) were evaluated according to the following method. The results are shown in Tables 3 and 4.
[0068] (Electrical conductivity (resistivity)) Immediately after production, the laminate was cut into a size of 2.5 cm × 5 cm, and the conductivity was measured by the four-probe method using Loresta GX MCP-T700 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with JIS-K7194. The conductivity is shown in Tables 3 and 4 as a relative value when the conductivity of Comparative Example 1 is set to 1.
[0069] (Seebeck coefficient) Immediately after production, the laminate was cut into a size of 3 mm × 10 mm, and the Seebeck coefficient (μV / K) at 80° C. was measured using a ZEM-3LW manufactured by Advance Riko Co., Ltd. Tables 3 and 4 show the relative values when the Seebeck coefficient of Comparative Example 1 was set to 1.
[0070] (Stability over time) The laminate immediately after preparation was left to stand for 10 days in an environment of 25°C and 50% humidity, and then the Seebeck coefficient was measured under the same conditions as above. The rate of change in the Seebeck coefficient from the Seebeck coefficient of the laminate immediately after preparation (the Seebeck coefficient listed in Table 4) was obtained and evaluated based on the following criteria. The smaller the rate of change in the Seebeck coefficient, the better, and a rate of change of more than 50% is poor. 1: The rate of change in the Seebeck coefficient is 10% or less. (Very good) 2: The rate of change in the Seebeck coefficient is greater than 10% and less than 20% (good). 3: The rate of change in the Seebeck coefficient is greater than 20% and less than 30%. (Usable) 4: The rate of change in the Seebeck coefficient is greater than 30% and less than 50%. (Usable) 5: The rate of change in the Seebeck coefficient is greater than 50%. (Poor)
[0071] As shown in Tables 3 and 4, the thermoelectric conversion material of the present invention exhibited high electrical conductivity and Seebeck coefficient. Furthermore, it was confirmed that the material had excellent stability over time under room temperature and constant humidity conditions. This is believed to be because compound (A) and / or a salt of compound (A) is stably adsorbed to conductive material (B). Furthermore, it is presumed that the addition of polymer (C) further enhances the adsorption of compound (A) and / or a salt of compound (A) to conductive material (B), suppressing aggregation of conductive material (B) and adsorption of moisture to conductive material (B), allowing the compound (A) and / or a salt of compound (A) to exist stably in the thermoelectric conversion material.
[0072] <Manufacturing of thermoelectric conversion elements> The above dispersion liquid was applied onto a PET film having a thickness of 50 μm, and five thermoelectric conversion layers having a thickness of 20 μm and a shape of 5 mm×30 mm were prepared at intervals of 10 mm. Next, four silver circuits (electrodes) having a thickness of 10 μm and a shape of 5 mm×33 mm were prepared using silver paste so that each thermoelectric conversion layer was connected in series, and thermoelectric conversion elements were manufactured. As the above silver paste, REXALPHA RA-FS 074 manufactured by Toyo Ink Co., Ltd. was used. When the electromotive force of each thermoelectric conversion element was measured, it was confirmed that the thermoelectric conversion elements manufactured using the dispersion liquids manufactured in Examples 1 to 25 all had a superior Seebeck coefficient to the thermoelectric conversion element manufactured using the dispersion liquid manufactured in Comparative Example 1.
[0073] [Table 1]
[0074] [Table 2]
[0075] [Table 3]
[0076] [Table 4]
Claims
1. A thermoelectric conversion material comprising a compound (A) represented by the following general formula (1) (excluding the case where the compound (A) is a polymer dispersant represented by the following general formula (2)) and / or a salt of the compound (A), a conductive material (B), and a polymer (C), wherein the conductive material (B) is at least one selected from the group consisting of carbon nanotubes, carbon black, and graphene, and the polymer (C) contains a polymer containing a monomer unit derived from (meth)acrylonitrile, or polyvinylpyrrolidone. 【Chemistry 1】 [In general formula (1), R 1 ~R 5 R each independently represents a hydrogen atom, an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent. 1 and R 2 Or R 3 and R 4 may be bonded to each other to form a ring, but R 1 and R 2 and R 3 and R 4 However, they do not form a ring at the same time. General formula (2) 【Chemistry 2】 [In general formula (2), R 6 represents a (m+n)-valent linking group. 7 represents a single bond or a divalent linking group. 1 R represents a monovalent organic group containing at least one moiety selected from an organic dye structure, a heterocyclic structure, an acidic group, a group having a basic nitrogen atom, a urea group, a urethane group, a group having a coordinating oxygen atom, a hydrocarbon group having 4 or more carbon atoms, an alkoxysilyl group, an epoxy group, an isocyanate group, and a hydroxyl group. 8 represents a single bond or a divalent linking group. 1 represents a non-conjugated polymer skeleton, m represents an integer of 1 to 8, n represents an integer of 2 to 9, and m+n is an integer of 3 to 10. When m is 2 or more, m P 1 and R 8 may be the same or different. 1 and R 7 may be the same or different.
2. 2. The thermoelectric conversion material according to claim 1, wherein the content of the polymer (C) is 5 to 100 mass % based on the total amount of the conductive material (B).
3. A thermoelectric conversion element comprising a thermoelectric conversion film comprising the thermoelectric conversion material according to claim 1 or 2 and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other.
Citation Information
Patent Citations
Aqueous thermochemical battery of high Seebeck coefficient and a device
CN109616678A
Continuous ceramic nanofibers, manufacturing method, and apparatus using the same
JP2010539349A
Thermoelectric conversion material and thermoelectric conversion element
JP2021103743A
N-type doping agent having excellent thermostability, and n-type doping method of nanocarbon material
JP2022135933A
Solid-state assembly of layers and an electric device comprising such assembly
US20130175513A1